An Analysis of Some Causal Factor Difficulties in Speaking English Ability at the Member Destorel English Club of Senior High School 8 Kota Jambi - Sebrina Hendri Zahir; Suyadi Suyadi; Kartika Dewi (JELT: Journal of English Language Teaching, 2022)
This study aims to determine analyze some students' ability about learning English in Destorel English Club of senior high school 8 in the city of Jambi. This research is a mix method research. The data collection technique was obtained through interview and recorded. The results showed that according to students learning English is very easy to understand if students want to learn to understand it, the interest of students of senior high school 8 Jambi city in receiving learning is also supported by learning support facilities such as books, English dictionaries, and other online English dictionary sites. In addition, the assignment given by the teacher also raises student ability.  Based on the research results, it can be concluded that according to students speaking ability in speaking English is very easy. Students' difficulties in receiving learning is also supported by supporting facilities for learning English such as books and dictionaries. Teachers always use two languages to interact with their students in learning English, namely by mixing Indonesian. Students always actively ask teachers and friends about learning English that students do not know, and students do not apply English in their daily life due to lack of vocabulary and lack confidence in interacting with other people in using English.